2017
DOI: 10.1038/srep43060
|View full text |Cite
|
Sign up to set email alerts
|

A novel thymoma-associated autoimmune disease: Anti-PIT-1 antibody syndrome

Abstract: Anti-PIT-1 antibody syndrome has recently been reported and characterized by acquired growth hormone (GH), prolactin (PRL), and thyroid-stimulating hormone (TSH) deficiencies associated with autoimmunity to a pituitary specific transcription factor PIT-1, which plays an essential role in GH-, PRL-, and TSH-producing cells. Although circulating anti-PIT-1 antibody and PIT-1-reactive cytotoxic T cells (CTLs) were detected in the patients, the pathophysiology and precise mechanisms for the autoimmunity remain unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…ELISPOT assays were performed using ELISpotPRO for Human IFN-γ (Mabtech, RRID:AB_2877719) [ 26 ], following the manufacturer’s instructions as previously described [ 2 , 6 ]. Briefly, a total of 2.5 × 10 5 isolated PBMCs were seeded into each well and incubated with recombinant PIT-1 protein (10 µg/mL, Santa Cruz Biotechnology) in 96-well microtiter plates precoated with 10 μg/mL of antihuman IFN-γ antibody [ 26 ] for 40 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ELISPOT assays were performed using ELISpotPRO for Human IFN-γ (Mabtech, RRID:AB_2877719) [ 26 ], following the manufacturer’s instructions as previously described [ 2 , 6 ]. Briefly, a total of 2.5 × 10 5 isolated PBMCs were seeded into each well and incubated with recombinant PIT-1 protein (10 µg/mL, Santa Cruz Biotechnology) in 96-well microtiter plates precoated with 10 μg/mL of antihuman IFN-γ antibody [ 26 ] for 40 hours.…”
Section: Methodsmentioning
confidence: 99%
“…In previous cases of anti–PIT-1 hypophysitis associated with thymoma, ectopic expression of PIT-1 was observed in the tumor tissue [ 6 ]. Therefore, we examined the DLBCL tissue in case 1.…”
Section: Case Presentationmentioning
confidence: 99%
“…Several APA have been identified and, despite background issues and the absence of universal standardization, indirect immunofluorescence remains the preferred method for their identification (for review see Guaraldi et al 2017). In some cases, clinical correlates between APA and hormone deficiencies have been reported, such as GH/TSH/PRL insufficiency in the setting of an anti-Pit syndrome (Bando et al 2017).…”
Section: Part I: Autoimmune Lymphocytic Hypophysitis (Lyh) In Systemimentioning
confidence: 99%
“…AI endocrinopathies and gastritis have also been recently associated with the "anti-Pit1 syndrome" which therefore enter the spectrum of APS. Importantly, this rare syndrome was recently associated with the presence of a thymoma, ectopic expression of Pit1 in the thymus may be causative, and thymectomy has proven to reduce the concentrations of anti-Pit-1 antibodies (Bando et al 2017).…”
Section: Lyh In Autoimmune Polyendocrine Syndromes (Aps)mentioning
confidence: 99%
“…PIT-1 plays an essential role in the differentiation of somatotrophs, lactotrophs, and thyrotrophs in the anterior pituitary and regulates the expression of GH, PRL, and TSH. Recently, it has been reported that breakdown of immune tolerance toward PIT-1 is caused by aberrant expression of PIT-1 protein in the thymoma [3]. In addition, circulating PIT-1–reactive cytotoxic T lymphocytes (CTLs) were detected in patients with anti–PIT-1 antibody syndrome, and the infiltration of these cells was observed in the pituitary, indicating that CTLs play a pivotal role in the development of the syndrome [4].…”
mentioning
confidence: 99%